Jesse Stone : Innocents Lost - Harmon, Robert; Selleck, Tom, 1945-; Baker, Kathy, 1950-; Blum, Mark, 1950-; Parker, Robert B., 1932-2010 (Culver City, Calif. : Sony Pictures Home Entertainment, 2011)
After being suspended Chief Stone is drawn back into the police force by a series of murders taking place in Boston.
Based on the novels by Robert B. Parker.
Tom Selleck, Kathy Baker, Mark Blum.
TV rating: Not rated.
DVD, Dolby digital 5.1 surround.
In English with optional English or French subtitles.
Closed-captioned.
Keywords: Parker, Robert B., -- 1932-2010 -- Television adaptations; Stone, Jesse (Fictitious character) -- Drama; Police -- Massachusetts -- Drama; Criminal investigation -- Drama; Made-for-TV movies; Detective and mystery television programs; Video recordings for the hearing impaired; Fiction television programs; Based on the book; Police television programs; Detective television programs; Mystery television programs